Teologi Pluralisme dalam Persfektif Injili - David Agus Haryono (Sekolah Tinggi Teologi Borneo, 2024)
Abstract: This journal aims to present evangelical identity in relation to the task of theology today. Evangelicalism is a movement that emphasizes belief in orthodox Christian doctrines as well as the inner change that comes in outward action. Its theological identity has historically been characterized: belief in the highest authority of the Bible, the importance of Christ's redemption, a change of heart, and evangelism. Simultaneously, these four identity characteristics serve as a fence and criterion for judging what kind of of theological development is acceptable within the evangelical movement. So that the role in the development of Evangelical Theology still maintains its identity as Evangelicals 1.Keywords: evangelicals, movement, identity, theology, IndonesiaAbstrak: Jurnal ini bertujuan untuk memaparkan identitas Injili dalam kaitannya dengan tugas berteologi pada masa kini. Injili adalah gerakan yang menekankan kepercayaan pada doktrin-doktrin ortodoks Kristen serta perubahan di dalam batin yang muncul di dalam tindakan keluar. Identitas teologisnya secara historis berkarakteristik: kepercayaan pada otoritas tertinggi Alkitab, pentingnya penebusan Kristus, perubahan di dalam hati, serta penginjilan. Secara simultan, empat karakter identitas ini berfungsi sebagai pagar dan kriteria untuk menilai perkembangan teologi seperti apa yang dapat diterima di dalam gerakan Injili. Sehingga peran dalam perkembangan Teologi Injili tetap menjaga identitasnya sebagai kaum injili 1.Kata kunci: kaum Injili, gerakan, identitas, teologi, Indonesia.